Detection and epidemiological progress of quiescent avocado diseases - Fischer, Ivan Herman; Moraes, Matheus Froes de; Firmino, Ana Carolina [UNESP]; Amorim, Lilian (Univ Federal Santa Maria, 2019)
One of the major problems in the commercialization of avocados is the incidence of postharvest diseases, especially anthracnose (Colletotrichum spp.) and stem-end rot (Lasiodiplodia theobromae, Fusicoccum aesculi and Neofusicoccum spp.). As there is a lack of epidemiological information on these pathosystems, the objective of this study was to establish a method to detect quiescent infections and characterize their temporal progression and spatial pattern in a commercial orchard. Detection of quiescent infections was evaluated in flowers and fruits that were immature and in commercial harvest stage, treated with paraquat, ethrel or water. Treatment of flowers and immature fruits with paraquat led to rapid detection of Colletotrichum spp. In two seasons of a 'Hass' avocado orchard, the incidence of diseases was evaluated from open flowers to fruit harvest, totaling 11 evaluations at biweekly intervals. When fruits reached the harvest stage, the spatial distribution of diseased fruits in the trees was evaluated by means of dispersion index and modified Taylor's law. Considering the evaluation of temporal disease progression, anthracnose was the most important disease, presenting a high initial incidence of 60 and 86% diseased flowers in the two seasons, respectively, while fruits showed an average disease incidence of 70 and 87%, respectively. Stem-end rot was observed only in fruits since the beginning of their development and presented low incidence (<8% fruits), significantly inferior to that of anthracnose. The diseases showed random dispersion within the trees, indicating that their initial inoculum is evenly distributed in the plants.
Keywords: Persea americana; postharvest rot; epidemiology